A Systematic Literature Review on Nutritional Meals for School Children and the Implications for Public Policy in Indonesia - Nonnytha Mahananny; Wahyu Aditama Putra Mukti Wibawa; Maria Carisita Suci Puspa Pranasari; Kurnia Aviati; Irine Puspita Sasmitaningsih (Green Publisher Indonesia, 2026)
This study aims to evaluate the nutritional needs of school children in relation to the Free Nutritious Eating (MBG) policy in Indonesia through a systematic literature review approach. The study was conducted on 26 scientific articles from various countries selected using the PRISMA 2020 method, with the inclusion criteria set include: (1) articles in the last ten years (2015–2025), (2) articles that explicitly discuss the nutritional needs of elementary to secondary school children, (3) articles that examine the contribution of school food programs to the fulfillment of children's nutrition, and (4) studies that are available in full text and written in English. The results show that school meals consistently make a significant contribution to meeting the needs of energy, protein, iron, calcium, fat, fiber and vitamin D, as well as positively impacting children's cognitive function and reducing the consumption of ultra-processed foods, especially in low-socioeconomic groups. In addition, it was found that the success of the program was greatly influenced by the diversity of menus, children's preferences, physical activity, and public policy support. This research makes an important contribution in formulating evidence-based MBG policies that take into account actual nutritional needs, socio-cultural contexts, and behavioral dynamics of children. In conclusion, MBG has great potential as a national strategy to improve the nutritional status and equal access to food for school children, but its successful implementation requires a multidimensional approach and advanced local studies.